NUMERICAL SIMULATION OF TEMPERATURE DISTRIBUTION ON METAL CASTING IN VERTICAL SOLIDIFICATION - Stieven, G. M.; Soares, D. R.; Oliveira, E. P.; Lins, E. F. (Revista de Engenharia Térmica, 2018)
The metals and alloys solidification can be defined as a transient heat transfer process. A liquid/solid transformation is followed by thermal energy liberation, with a movable boundary separating two phases with different thermophysical properties. The solidification is of great interest to mechanical and chemical engineers. It is a non-linear transient phenomenon, where heat transfer between the casting and the mold plays a important role. This paper aims to propose a study of heat flow from the casting to the mold using a numerical technique to compute the temperature history of all points inside the casting. The cooling process consists of water-cooled mold with heat being extracted only from the bottom, resulting in unidirectional vertical solidification. The ANSYS software was used to obtain the temperature distribution in the casting. Good agreement was obtained when the simulation results were compared with the experimental data.